Evaluating the risk of climate change-induced aflatoxin contamination in groundnuts and maize: Result of modeling analyses in six countries - Thomas, Timothy S.; Robertson, Richard D.; Boote, Kenneth J. (International Food Policy Research Institute, 2019)
This policy note summarizes research that assessed the likely impact of climate change on aflatoxin contamination in groundnuts (in Burkina Faso, Niger, and Nigeria) and in maize (in Burkina Faso, Honduras, Guatemala, Nepal, Niger, and Nigeria), and the impact of temperature, precipitation, and soil types on aflatoxin contamination. A future goal is to improve the calibration of the modeling software utilized to enable its use as an early warning tool for aflatoxin hotspots.